BUDAYA POPULER DAN MUSLIM FANS KOREA: CONSUMERS’ EXPERIENCE PADA KOREAN FOOD HALAL DI HANA GIMBAB YOGYAKARTA - Musriaparto Musriaparto; Junaidi Junaidi; Maya Kholida (Jurnal Analisa Sosiologi, 2024)
Korean culture has become part of popular culture, giving birth to the Korean wave phenomenon. In Indonesia, Muslims are involved as fans of Korean popular culture, including in their food consumption. For this reason, this research aims to explore the experiences of Muslim Korean fans with halal Korean food and how they negotiate Islam with Korean popular culture through food. This research is field research using descriptive qualitative research methods. The research was conducted at waroeng Hana Gimbab Yogyakarta by conducting interviews with six consumers. The results of this research explain that Muslims' involvement in popular culture as Korean fans shapes their social identity as Muslims and Korean fans. This is done to participate in emerging cultural trends. Apart from that, popular culture also creates a culture of consumerism for Muslim Korean fans, where they consume Korean food as a form of merging with Korean popular culture. In this context, there are two negotiation patterns carried out by Korean Muslim fans regarding Korean food. First, there are strict negotiations, where the encouragement of piety encourages them to adopt halal consumption patterns. Second, there are looser negotiations, where some Muslim Korean fans do not really question the halalness of food and are more free to experiment with consuming Korean food.